A PROSPECTIVE STUDY OF BODY MASS INDEX AND THE RISK OF DEVELOPING HYPERTENSION IN MEN - Gelber, Rebecca P. (2007)
BACKGROUND: Although obesity is known to increase the risk of hypertension, few studies have prospectively evaluated body mass index (BMI) across the range of normal weight and overweight as a primary risk factor. METHODS: In this prospective cohort, we evaluated the association between BMI and risk of incident hypertension. We studied 13,563 initially healthy, non-hypertensive men who participated in the Physicians’ Health Study. We calculated BMI from self-reported weight and height and defined hypertension as self-reported systolic blood pressure (BP) ≥140 mmHg, diastolic BP ≥90 mmHg, or new antihypertensive medication use. RESULTS: After a median 14.5 years, 4920 participants developed hypertension. Higher baseline BMI, even within the “normal” range, was consistently associated with increased risk of hypertension. Compared to participants in the lowest BMI quintile (<22.4 kg/m(2)), the relative risks (95% confidence interval) of developing hypertension for men with a BMI of 22.4–23.6, 23.7–24.7, 24.8–26.4, and >26.4 kg/m(2) were 1.20 (1.09–1.32), 1.31 (1.19–1.44), 1.56 (1.42–1.72), and 1.85 (1.69–2.03), respectively (P for trend, <0.0001). Further adjustment for diabetes, high cholesterol, and baseline BP did not substantially alter these results. We found similar associations using other BMI categories and after excluding men with smoking history, those who developed hypertension in the first 2 years, and those with diabetes, obesity, or high cholesterol at baseline. CONCLUSION: In this large cohort, we found a strong gradient between higher BMI and increased risk of hypertension, even among men within the “normal” and mildly “overweight” BMI range. Approaches to reduce the risk of developing hypertension may include prevention of overweight and obesity.